The socio-educational model of second language acquisition: The Turkish context - KURT TİFTİK, GÖKÇE (ELSEVIER SCIENCE BV, 2010)
In the socio-educational model the complex of attitudes toward the learning situation and motivation reflects an integrative motive that promotes language learning. Whether integrative motive exists in EFL settings or whether it is more relevant to ESL contexts has been an issue of debate for years. The present study aims to expand the current knowledge on this issue and investigate the generalizability of the socio-educational model to the Turkish context. In the research conducted with Turkish EFL learners reliability and construct validity of the AMTB, as well as correlates of the major elements of the model with grades in English and their perceived language competence were analyzed. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Socio-educational model; motivation; EFL